Design of a Mobile Mechanical Structure for Agricultural Robots. - Musinguzi, Bosco (Kabale University, 2023)
This report covers the design of a mobile mechanical structure for agricultural robots that will fit in the current crop spacing using the extendable link mechanism based on a four bar link mechanism linear actuator. This covers the analysis of the steering, suspension spring, singularity with its maximum and minimum angles, wheel arrangement, selection and design. The structural analysis using ANSYS is included to evaluate the strength of the mechanical structure used when in its worst working conditions and the results were presented and included in this report. The problem of farmers buying a mechanical platform for different crop spacing will be solved by this mechanical structure hence reducing the costs involved in agricultural activities and this will be the motivation factor for farmers to practice agricultural activities using one mobile mechanical structure which will solve the problem of unreliable human labour and encourage farmers to practice modernized and precision agriculture. The related work from the related projects is included with n this report since such technology is not new but it needed modification to fit in the current agricultural activities to reduce on the costs involved in carrying out agricultural works. Since there is no economical alternative for food agriculture sector needs serious attention to cater for the increasing global population.